2022
DOI: 10.3389/fmicb.2021.828765
|View full text |Cite
|
Sign up to set email alerts
|

Updated HIV-1 Consensus Sequences Change but Stay Within Similar Distance From Worldwide Samples

Abstract: HIV consensus sequences are used in various bioinformatic, evolutionary, and vaccine related research. Since the previous HIV-1 subtype and CRF consensus sequences were constructed in 2002, the number of publicly available HIV-1 sequences have grown exponentially, especially from non-EU and US countries. Here, we reconstruct 90 new HIV-1 subtype and CRF consensus sequences from 3,470 high-quality, representative, full genome sequences in the LANL HIV database. While subtypes and CRFs are unevenly spread across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…The consensus sequences of HIV proteins and their conservation studies allow a better understanding of structural, functional, and immunogenic potential differences across HIV-1 groups, subtypes, sub-subtypes, and recombinants and have been previously analyzed in other HIV-1 proteins ( Li et al, 2013 ; Sliepen et al, 2019 ; Zhang et al, 2021 ). A recent work by Linchangco et al reconstructed 90 HIV-1 subtype and CRF consensus sequences from 3,470 full HIV genomes downloaded from LANL ( Linchangco et al, 2021 ). Our study updates and expands the knowledge regarding HIV Pol variability, including 59,733 PR, 6,437 RT, and 6,059 IN sequences from more than 100 different variants, including all the currently available HIV-1 groups, subtypes, and CRF in LANL.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus sequences of HIV proteins and their conservation studies allow a better understanding of structural, functional, and immunogenic potential differences across HIV-1 groups, subtypes, sub-subtypes, and recombinants and have been previously analyzed in other HIV-1 proteins ( Li et al, 2013 ; Sliepen et al, 2019 ; Zhang et al, 2021 ). A recent work by Linchangco et al reconstructed 90 HIV-1 subtype and CRF consensus sequences from 3,470 full HIV genomes downloaded from LANL ( Linchangco et al, 2021 ). Our study updates and expands the knowledge regarding HIV Pol variability, including 59,733 PR, 6,437 RT, and 6,059 IN sequences from more than 100 different variants, including all the currently available HIV-1 groups, subtypes, and CRF in LANL.…”
Section: Discussionmentioning
confidence: 99%
“…We generated consensus sequences for subtypes/CRFs for each sampling period, except when there were fewer than 10 sequences available (Table S2; File S4 to S6). We compared our derived consensus sequences with the consensus sequences available at LANL: the recently generated LANL 2021 consensus sequences (based on 3,470 high-quality, representative HIV-1 genomes selected from the 2019 filtered web alignment) ( 22 ) and the previously available LANL 2004 consensus sequences (similarly derived from a filtered set of sequences available at the time). Compared with the LANL 2004 Env consensus sequence, our consensus sequences showed a mean of 37 (only subtype B), 30.29 (min = 11, max = 49), 33.50 (18,52), and 35.86 (27,43) mismatched residues between the consensuses we generated for 1980–1990, 1991–2000, 2001–2010, and 2011–2020, respectively, which decreased to 24, 26 (17,33), 24.80 (11,40), and 30.33 (15,46) when compared with the new LANL 2021 consensus sequences ( 11 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent molecular epidemiology studies systematically evaluated the proportion of each subtype and CRF globally and regionally and shifts in these proportions over time ( 6 , 7 ). Linchangco and colleagues at the LANL HIV database, which maintains curated data sets of HIV-1 sequences (among other resources), recently updated the consensus for all HIV-1 subtypes and CRFs using 3,470 high-quality, representative HIV-1 genomes selected from the LANL HIV database 2019 filtered web alignments ( 22 ). They showed that an average of 2.3% (range 0.8%–10%) of sites changed across the consensus genomes designed in 2002 and in 2021 (with similar proportions of substitutions vs. insertions or deletions) and concluded that 2021 consensus sequences were good representations of the typical subtype/CRF genomes.…”
Section: Introductionmentioning
confidence: 99%
“…There are 4 recognized requirements for subtype references classification: (1) one or more complete sequence(s); (2) at least three epidemiologically unrelated isolates; (3) distinct clusters in a phylogenetic tree; (4) exclusion of intersubtypic recombination, whether the components were classified or not (22, 24, 25). Because sequences included in Subtype Reference Alignments have been strictly screened and recognized as standard references and widely used in related research of the field (51-53), they were named gold-standard sequences in this study. We found that among the 302 screened 5’ LTRs with full-length sequences, 20 sequences belong to gold-standard sequences (Supplementary Dataset 4).…”
Section: Resultsmentioning
confidence: 99%